Evaluating the effect of low and high temperature mode of subcritical water pretreated empty fruit bunches on co-digestion performance and kinetic study for methane production - Hamzah, Adila Fazliyana Aili (Malaysian Palm Oil Board, 2023)
Anaerobic digestion of oil palm empty fruit bunches (EFB) is considered an effective method for non-renewable energy substitution through biogas production. However, lignocellulosic recalcitrance structure of EFB is one of the main difficulties in achieving high biogas production for anaerobic co-digestion with palm oil mill effluents (POME). In this study, EFB was pretreated with subcritical water (SCW) at low (120⁰C) and high (180⁰C) temperatures for 10 to 30 minutes to enhance biogas production. The characteristics of EFB after SCW pre-treatment were evaluated to identify changes in physicochemical characteristics. The combination pre-treatment of 180⁰C for 10 minutes with 546.18 mL/g volatile solid (VS) biogas yield and 421.41mL CH4/g VS methane yield revealed the highest biogas production. Meanwhile, co-digestion of SCW pretreated EFB with POME led to a removal of more than 66% VS. The sugars released were analysed in liquid fraction of SCW pre-treated EFB where glucose, xylose, cellobiose, mannose and galactose were detected. Notably, kinetic study of biogas production of pre-treated EFB using modified Gompertz model revealed that pre-treatment improved the lag phase, and highest biogas production rate was observed at 19.80 mL/g VS. day. In conclusion, co-digestion of EFB with POME for methane production can be improved with the use of SCW pre-treatment.